Tourism green growth through technological innovation - Jo Y; Kim MJ; Yoon Y-S; Hall CM (Taylor and Francis Group, 2025)
The work seeks to assess the effect of technological innovation on the green growth of tourism across five continental regions using the STochastic estimation of Impacts by Regression on Population, Affluence, and Technology (STIRPAT) model. Employing panel Granger causality tests, panel vector autoregression, impulse response functions, and forecast error variance decomposition, the research reveals the bidirectional causal relationship between green growth and technological innovation, emphasizing the importance of technological innovation for tourism. The study utilizes panel data from 126 countries spanning from 2010 to 2021 and employs a range of econometric techniques. These methods allow for a thorough examination of the causal relationships, short and long term impacts, and the relative importance of different variables on tourism related green growth. The findings further highlight the contribution of green growth to developing a sustainable economy and emphasize the significance of sustainable tourism as a significant factor in green growth policies. The study expands the application of STIRPAT to the green growth and tourism relationship and provides practical implications for stakeholders.
Keywords: Green growth; tourism; technological innovation; STIRPAT; sustainability; econometric analysis